ANALISIS KANDUNGAN ZAT PEMANIS SAKARIN DAN SIKLAMAT PADA MINUMAN YANG DI PERDAGANGKAN DI SEKOLAH DASAR DI KELURAHAN WUA-WUA KOTA KENDARI - Setiawan, Egi Aldi (Jurnal Sains dan Teknologi Pangan, 2016)
The research objective was to determine the content of synthetic sweeteners of saccharine and cyclamate in the beverages traded in the canteens of elementary school in Wua-Wua Kendari. This research employed a descriptive method. The results showed that there were no saccharine found in the drinks traded in the elementary school canteen in this area.  However, a sweetener of cyclamate was found in the drink, with varied concentration.  The highest cyclamate content of 333 mg/L was found in the drinks traded in the elementary school of SD 10; while the lowest cyclamate content of 78 mg/L was found in the elementary school of SD 4. These cyclamate contents were still below the levels allowed by BPOM (Indonesian Food and Drug Administration). Although the artificial sweetener present was still below the maximum limit, the Regulation of the Indonesian Ministry of Health, had recommended that the artificial sweeteners was only intended for low-energy products, or for people with diabetes mellitus and not for general consumption, especially not for children. Keywords: saccharin, cyclamate, syrup, organoleptic, precipitation, weighing